Forgetting the Alamo, Or, Blood Memory A Novel - Pérez, Emma (University of Texas Press, 2021)
This literary adventure takes place in nineteenth-century Texas and follows the story of a Tejana lesbian cowgirl after the fall of the Alamo. Micaela Campos, the central character, witnesses the violence against Mexicans, African Americans, and indigenous peoples after the infamous battles of the Alamo and of San Jacinto, both in 1836. Resisting an easy opposition between good versus evil and brown versus white characters, the novel also features Micaela's Mexican-Anglo cousin who assists and hinders her progress. Micaela's travels give us a new portrayal of the American West, populated by people of mixed races who are vexed by the collision of cultures and politics. Ultimately, Micaela's journey and her romance with a black/American Indian woman teach her that there are no easy solutions to the injustices that birthed the Texas Republic. This novel is an intervention in queer history and fiction with its love story between two women of color in mid-nineteenth-century Texas. Pérez also shows how a colonial past still haunts our nation's imagination. The battles of the Alamo and San Jacinto offered freedom and liberty to Texans, but what is often erased from the story is that common people who were Mexican, Indian, and Black did not necessarily benefit from the influx of so many Anglo immigrants to Texas. The social themes and identity issues that Pérez explores-political climate, debates over immigration, and historical revision of the American West-are current today